Surgical technician - Primm, E. Russell, 1958-; Quinlan, Kathryn A. (Mankato, Minn. : Capstone Books, 1998)
Outlines the educational requirements, duties, salary, employment outlook, and possible future positions of surgical technologists.
includes index.
Keywords: Surgical technology -- Vocational guidance -- Juvenile literature; Surgical technology -- Vocational guidance; Vocational guidance